1673 Accuracy and prognostic value of physiologist-led stress echocardiography for coronary disease. (17th January 2020) - Khan, J N; Griffiths, T; Sandhu, K; Cabezon, S; Kwok, C S; Baig, S; Naneishvili, T; Lee, V C K; Pasricha, A; Robins, E; Kanagala, P; Butler, R; et al.
Abstract: Funding Acknowledgements: No funding sources Background: Cardiac physiologist-led stress echocardiography (PLSE) services provide potential for expansion of SE services and increased productivity for cardiologists. There is no published data on the accuracy or prognostic value of PLSE. Purpose: To assess and compare the accuracy and prognostic value of PLSE and cardiologist-led stress echocardiography (CLSE) for CAD assessment Methods: Retrospective study of 898 subjects undergoing PLSE (n = 393) or CLSE (n = 505) for CAD assessment using exercise or dobutamine. For accuracy assessment, the primary outcome was the ability of stress echocardiography to identify significant CAD on invasive angiography (ICA). Incidence of 24-month non-fatal myocardial infarction (MI), total and cardiac mortality, revascularisation and combined major adverse cardiac events (MACE) were assessed. Results: Demographics, comorbidities, CAD predictors and cardiac medications were matched between the PLSE and CLSE groups. PLSE had high sensitivity, specificity, positive and negative predictive value and accuracy (85%, 74%, 69%, 88%, 78% respectively). PLSE accuracy measures were similar and non-inferior to CLSE. There was a similar incidence of individual and combined outcomes in PLSE and CLSE subjects. Negative stress echocardiography conferred a low incidence of non-fatal MI (PLSE 1.4% vs. CLSE 0.9%, p = 0.464), cardiac mortality (0.6% vs. 0.0%, p = 0.277) and MACE (6.8% vs. 3.1%, p = 0.404). Conclusion: This is the largest study of PLSE accuracy and first study of the prognostic value of PLSE. PLSE demonstrates high and non-inferior accuracy compared with CLSE for CAD assessment. Negative PLSE and CLSE confer a similarly very low incidence of cardiac outcomes, confirming for the first time the important prognostic value of PLSE.